Pemutusan Hubungan Kerja Akibat Pelanggaran Berat Pasca Terbitnya UU RI Nomor 06 Tahun 2023 Tentang Cipta Kerja - Nur, Fahroni; Sudarmanto, Kukuh; Arifin, Zaenal; Sukrisno, Wijayono Hadi (Journal Juridisch, 2024)
The purpose of this research is to analyze and understand the legal protection of workers whose employment relationship is terminated and the legal liability of employers who carry out layoffs according to Law Number 06 of 2023 concerning Job Creation. The urgency of this research requires regulations regarding layoffs due to serious or urgent violations contained in the Job Creation Law and its supporting laws and regulations. Employers carry out layoffs on the grounds of serious or urgent violations without going through a criminal law process that has permanent legal force. This decision was further strengthened by the existence of SEMA Number 03 of 2015 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber where layoffs can be carried out without having to wait for a legally binding court decision. This research uses a juridical-normative method, through a statutory legal approach. The results of research by workers who have been laid off and representatives of workers who have suffered losses due to serious or urgent violations have examined legal regulations regarding the Job Creation Law and PP 35 of 2021, Article 52 which regulates urgent violations, so that workers cannot be a termination by the Company without waiting for legally binding court, and the Employer carries out the rules following the previous rules regarding serious violations. Tujuan penelitian ini menganalisis dan memahami perlindungan hukum tenaga kerja yang diputus hubungan kerjanya dan pertanggungjawaban hukum pengusaha yang melakukan PHK menurut UU Nomor 06 Tahun 2023 tentang Cipta Kerja. Urgensi penelitian ini perlu pengaturan mengenai PHK karena pelanggaran berat atau bersifat mendesak yang terdapat pada UU Cipta Kerja dan peraturan perundangan pendukungya. Pengusaha melakukan PHK dengan alasan pelanggaran berat atau bersifat mendesak tanpa melalui proses hukum pidana yang berkekuatan hukum tetap. Keputusan tersebut dikuatkan lagi dengan adanya SEMA Nomor 03 tahun 2015 tentang Pemberlakuan Rumusan Hasil Rapat Pleno Kamar MA dimana PHK dapat dilakukan tanpa harus menunggu putusan pidana berkekuatan hukum tetap. Penelitian ini menggunakan Metode yuridis-normatif, melalui pendekatan hukum perundang-undangan. Hasil penelitian pihak pekerja yang di PHK maupun perwakilan pekerja yang dirugikan karena pasal pelanggaran berat atau bersifat mendesak melakukan pengujian peraturan perundangan mengenai UU Cipta kerja dan PP 35 tahun 2021, pasal 52 yang mengatur mengenai pelanggaran bersifat mendesak, agar pekerja tidak dapat di PHK secara sewenang-wenang oleh Perusahaan tanpa menunggu keputusan pengadilan pidana yang bersifat mengikat, serta Pengusaha menjalankan aturan sesuai dengan aturan terdahulu mengenai pelanggaran berat.